Solid Biofuels for Energy A Lower Greenhouse Gas Alternative - Grammelis, Panagiotis (Green Energy and Technology,, 2011)
Climate change, environmental impact and declining natural resources are driving scientific research and novel technical solutions. Green Energy and Technology serves as a publishing platform for scientific and technological approaches to "green" - i.e., environmentally friendly and sustainable - technologies. While the main focus lies on energy and power supply, the series also covers green solutions in industrial engineering and engineering design. Green Energy and Technology is a monograph series addressing researchers, advanced students and technical consultants, as well as decision makers in industry and politics. The level presentation ranges from instructional to highly technical. Fossil fuels are widely used for electricity generation and heating, creating greenhouse gas emissions and other toxic pollutants, which should be minimised according to the most recent environmental legislation. The utilisation of solid fuels with biogenic origin could contribute to the minimisation of these emissions. Solid Biofuels for Energy presents the current status of the engineering disciplines in this specific area, providing an improved background on the energy exploitation options of solid biomass. Within this framework, all thematic priorities related to the solid bioenergy potential and standardisation, commercialised and emerging energy technologies, and quality of solid residues are presented. Special attention has been given to biomass co-firing with coal, since it has the highest potential for commercial application, while combustion and gasification are more promising for units of medium to small scale. This strong practical focus is evident throughout the book, particularly in discussions of: • international standards for solid biofuel specifications; • supply, cost and sustainability of solid biofuels; • technical issues and non-technical barriers in biomass/coal co-firing; and • biomass combustion and gasification characteristics. Solid Biofuels for Energy is an informative reference, written for researchers and postgraduate students working in the field of biomass. It can also be a useful guide for chemical and mechanical engineers, involved in the environment and energy production sectors.